TAZKIYATUN NAFS AL-GHAZALI SEBAGAI KRITIK ETIKA SPIRITUAL TERHADAP BUDAYA MEDIA SOSIAL KONTEMPORER - Nur rahmi Nurrahmi; Rina Rehayati; Ahmad Zikri (JURNAL AL-AQIDAH, 2026)
The rapid growth of social media has generated various ethical challenges, including digital narcissism, social validation culture, misinformation, cancel culture, and the decline of moral interactions in digital spaces. Although studies on Islamic digital ethics have expanded considerably, most have focused on digital literacy, communication ethics, and character education, while limited attention has been given to integrating Al-Ghazali's concept of tazkiyatun nafs as a spiritual ethical framework for addressing contemporary social media culture. This study aims to examine the relevance of Al-Ghazali's concept of tazkiyatun nafs as a critical perspective on contemporary social media practices and to propose a conceptual model of digital spiritual ethics grounded in Islamic values. This research employs a qualitative library research approach using content analysis. The primary sources consist of Al-Ghazali's major works, particularly Ihya' Ulum al-Din, supported by scholarly publications on Islamic digital ethics and social media selected based on their relevance, academic credibility, and thematic alignment with the research objectives. The analysis was conducted through thematic identification, conceptual categorization, interpretation of Al-Ghazali's thought, and conceptual synthesis of contemporary digital culture. The findings reveal that the stages of takhalli, tahalli, and tajalli provide a comprehensive ethical framework for understanding and addressing spiritual diseases emerging from social media culture. This study proposes a conceptual model of digital spiritual ethics that connects amradh al-qulub (spiritual diseases), self-purification, and the development of ethical digital behavior. Theoretically, the study enriches the discourse on Islamic digital ethics by integrating classical Sufi thought with contemporary digital challenges. Practically, the findings contribute to the development of Islamic education, spirituality-based digital literacy, and ethical social media practices.